Cross Talk between Inhibitory Immunoreceptor Tyrosine-Based Activation Motif-Signaling and Toll-Like Receptor Pathways in Macrophages and Dendritic Cells - Hirsch, Ivan; Janovec, Vaclav; Stranska, Ruzena; Bendriss-Vermare, Nathalie (Frontiers in Immunology, 2017)
The innate immune cells sense microbial infection and self-ligands, by pathogen recognition receptors (PRRs), such as toll-like receptors (TLRs) and regulatory receptors (RR) associated with immunoreceptor tyrosine-based activation motif (ITAM). Rapid activation and concerted action of PRRs signaling and feedback inhibitory mechanisms must be engaged to ensure the host defense functions and to prevent cytotoxicity associated with excessive activation. ITAM-associated RR can generate stimulatory or, paradoxically, inhibitory signals. The network of ITAM-associated RR, together with TLR-signaling pathways, are responsible for immunogenic or tolerogenic responses of macrophages and dendritic cells (DCs) to their microenvironment. In macrophages, TLR4 signaling is inhibited by low-avidity ligation of ITAM-associated receptors, while high-avidity ligation of ITAM-associated receptors results in potentiation of TLR4 signaling together with resistance to extracellular cytokine microenvironment signals. In contrast to macrophages, TLR7/9 signaling in plasmacytoid DC (pDCs) is inhibited by high-avidity ligation of ITAM-associated RR, while low-avidity ligation does not show any effect. Surprisingly, interference of ITAM-associated receptor signaling with TLR pathways has not been reported in conventional dendritic cells (cDCs). Here, we present an overview of molecular mechanisms acting at the crossroads of TLR and ITAM signaling pathways and address the question of how the high-avidity engagement of the ITAM-associated receptors in pDCs inhibits TLR7/9 signaling. Cellular context and spatio-temporal engagement of ITAM and TLR signaling pathways are responsible for different outcomes of macrophage versus pDC activation. While the cross-regulation of cytokine and TLR signaling, together with antigen presentation, are the principal functions of ITAM-associated RR in macrophages, the major role of these receptors in pDCs seems to be related to inhibition of cytokine production and reestablishment of a tolerogenic state following pDC activation. Pharmacologic targeting of TLR and ITAM signaling could be an attractive new therapeutic approach for treatment of chronic infections, cancer, and autoimmune and inflammatory diseases related to pDCs.